2022
DOI: 10.3390/en15124457
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Heat Transfer Coefficient, Thermal Effusivity and Mathematical Modelling of Drying Kinetics of a Partitioned Single Pass Low-Cost Solar Drying of Cocoyam Chips with Economic Assessments

Abstract: This study examines the heat and mass transfer coefficient, thermal effusivity, and other thermal properties of solar-dried cocoyam chips, as well as the drying kinetics. The research also assessed the economics of the solar dryer. For these reasons, a solar dryer with a partitioned collector was developed that creates a double airflow travel distance to delay the airflow inside the collector. The partitioning of the collector delays the airflow and helps to create more turbulence for the airflow with increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“…The solar radiation intensity varied from 103 to 616 W/m 2 with an average value of 374.87 W/m 2 . The peak solar radiation value is lower than 1013 W/m 2 obtained by Lamrani et al [ 41 ] in Morocco but the average value is higher than 368.38 and 303.6 W/m 2 recorded by Ndukwu et al [ 31 , 42 ] respectively in this area. These showed that the study location is a low solar intensity area which most time results in a longer period of drying using the solar dryer when compared to areas like Morocco.…”
Section: Resultscontrasting
confidence: 52%
“…The solar radiation intensity varied from 103 to 616 W/m 2 with an average value of 374.87 W/m 2 . The peak solar radiation value is lower than 1013 W/m 2 obtained by Lamrani et al [ 41 ] in Morocco but the average value is higher than 368.38 and 303.6 W/m 2 recorded by Ndukwu et al [ 31 , 42 ] respectively in this area. These showed that the study location is a low solar intensity area which most time results in a longer period of drying using the solar dryer when compared to areas like Morocco.…”
Section: Resultscontrasting
confidence: 52%
“…Among these renewable systems, solar thermal systems are becoming popular (Xiong et al, 2021a and2021 b). Its potential for decarbonization of the ecosystem and cost benefits has been presented in the literature (Ndukwu et al, 2022a, Simo-Tagne et al, 2019. Solar energy is available and well-distributed globally .…”
Section: Introductionmentioning
confidence: 99%
“…The value of the coefficient of determination R 2 is in the two cases, respectively, equal to 0.99 and 0.88. Furthermore, a regression analysis was carried out by means of the CurveExpert Professional 40 to evaluate the existing correlation between the heat flow difference exchanged by the panel and the internal temperature calculated as the mean temperature value of both panel sides. The measured positive and negative heat flow differences and the corresponding temperatures for all periods of the test were considered for each panel.…”
Section: Resultsmentioning
confidence: 99%